Restoration of Chemoresistance Mechanism by Novel Drug Therapies in Breast Cancer Cell Lines - Sarkar, Esha; Misra, Aparna; Mahdi, Abbas A.; Trivedi, Anchal; Khan, Afreen (Current Drug Therapy, 2021)
Chemoresistance is one of the biggest hurdles while treating cancer clinically. Due to its heterogeneous nature, complications of the chemoresistance mechanisms of breast cancer cannot be completely elucidated. Existing mechanisms of main-line drug treatment can slow down the process of malignancy with part and parcel called drug resistance. The combinatorial effect of several chemotherapeutic drugs, targeting different pathways at the same time, can work efficiently, yet the toxicity and drug-drug interaction remain intact. To overcome this hurdle, a number of strategies have been discovered, such as novel agents, drug carriers, and combination treatment, etc., which target mediated drug delivery systems; nanomedicine and the use of phytocompounds can transfer the drug particularly to the cancerous cells with minimal side effects to the neighboring healthy cells. The cell cycle checkpoint proteins and genes induced to the deranged cells can inhibit the resistance mechanism towards the drug. Modification of cell signaling pathways can also help to treat breast cancer chemoresistance mechanisms in the long run. This article reviews the execution and onset of chemoresistance in various cancers and discusses potential therapeutic approaches to deal with the resistance mechanism. This review summarizes the possible mechanisms and signaling pathways causing chemoresistance in breast cancer cell lines and discusses alternative therapy to overcome this issue under pre-clinical and clinical infrastructure.
Keywords: multi drug resistance